The influence of community social capital on pre-service teachers’ career calling: the mediating role of career exploration and the moderating effect of agreeableness - Su, Xiaomin; Ahmad, Anuar; Alias, Jamsari (Frontiers in Education, 2024)
This study aims to explore the mechanism of the influence of community social capital on preservice teachers' career calling, and examine the mediating role of career exploration and the moderating effect of agreeableness. Data were collected from 455 pre-service teachers in a local undergraduate normal college in Guangdong Province. The structural equation model was used for analysis. The results showed that there was a significant positive relationship between community social capital and career calling, career exploration played a mediating role, and agreeableness played a moderating role in the relationship between community social capital and career exploration. This finding provides valuable theoretical and practical support for colleges and universities to develop and design community service-learning education programs in order to promote pre-service teachers' career exploration, meet the individualized requirements of future teachers, and cultivate pre-service teachers' career calling.